K3 surfaces and their moduli - Faber, Carel; Farkas, Gavril; Geer, Gerard van der (Birkhäuser, 2016)
Introduction -- Samuel Boissière, Andrea Cattaneo, Marc Nieper-Wisskirchen, and Alessandra Sarti: The automorphism group of the Hilbert scheme of two points on a generic projective K3 surface -- Igor Dolgachev: Orbital counting of curves on algebraic surfaces and sphere packings -- V. Gritsenko and K. Hulek: Moduli of polarized Enriques surfaces -- Brendan Hassett and Yuri Tschinkel: Extremal rays and automorphisms of holomorphic symplectic varieties -- Gert Heckman and Sander Rieken: An odd presentation for W(E_6) -- S. Katz, A. Klemm, and R. Pandharipande, with an appendix by R. P. Thomas: On the motivic stable pairs invariants of K3 surfaces -- Shigeyuki Kondö: The Igusa quartic and Borcherds products -- Christian Liedtke: Lectures on supersingular K3 surfaces and the crystalline Torelli theorem -- Daisuke Matsushita: On deformations of Lagrangian fibrations -- G. Oberdieck and R. Pandharipande: Curve counting on K3 x E, the Igusa cusp form X_10, and descendent integration -- Keiji Oguiso: Simple abelian varieties and primitive automorphisms of null entropy of surfaces -- Ichiro Shimada: The automorphism groups of certain singular K3 surfaces and an Enriques surface -- Alessandro Verra: Geometry of genus 8 Nikulin surfaces and rationality of their moduli -- Claire Voisin: Remarks and questions on coisotropic subvarieties and 0-cycles of hyper-Kähler varieties.
Description based upon print version of record